Orbital Cellulitis with Exudative Retinal Detachment - Karki, Pooja; Pandey, Manish (Medical Journal of Shree Birendra Hospital, 2016)
Exudative retinal detachment occurs extremely rarely with orbital cellulitis. TB can affect majority of the structures of the eye with marked variability of the lesions. We herein report a 40 year old male who presented with acute left eye protrusion with sudden diminution of vision. On examination there was proptosis of the left eye with restricted extraocular movements. Exudative retinal detachment with subretinal abscess was present in the same eye. Magnetic Resonance Imaging (MRI) of brain showed right sided frontal lobe lesion suggestive of tuberculoma with positive Quantiferon - TB Gold test.